Analysis of Occupational Safety and Health Culture Through Students’ Awareness of Workplace Hazards: A Study of Clause 7.3 of ISO 45001:2018 - Kadek Adi Mahendra (International Journal of Curriculum Development, Teaching and Learning Innovation, 2026)
Laboratory environments in higher education institutions present significant occupational hazards, yet systematic safety management remains largely underdeveloped, particularly in specialized facilities such as the Highway Engineering Laboratory. This study aims to analyze the safety culture through the level of OSH awareness among Civil Engineering students at the Highway Engineering Laboratory of Universitas Lampung based on Clause 7.3 of ISO 45001:2018. A quantitative descriptive method was employed, with data collected from 150 students of the 2023 cohort using a total sampling technique and an 11-item Likert-scale questionnaire across five dimensions: OSH policy awareness, contribution to OSH, benefits of OSH performance, implications of non-conformance, and SOP observance. The results indicate an overall mean awareness score of 2.41 (Low), with the lowest scores recorded in OSH Policy Awareness (2.11) and SOP Observance (2.19), attributable to the confirmed absence of a formal OSH policy and documented SOP in the laboratory. These findings conclude that the laboratory has not fulfilled the foundational requirements of ISO 45001:2018, necessitating immediate development of formal safety documentation and structured OSH orientation programs